2023
DOI: 10.1101/2023.07.07.548145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Prokaryotic and Eukaryotic Microbiome of Pacific Oyster Spat is Shaped by Ocean Warming but not Acidification

Abstract: Pacific oysters (Magallana gigas, also known as Crassostrea gigas), the most widely farmed oysters, are under threat from climate change and emerging pathogens. In part, their resilience may be affected by their microbiome, which, in turn, may be influenced by ocean warming and acidification. Consequently, for three weeks, we exposed early-development Pacific oyster spat to different temperatures (18 and 24 °C) and pCO2 levels (800, 1600 and 2800 μatm) in a fully crossed design. Under all conditions, the micro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 117 publications
1
0
0
Order By: Relevance
“…In the present study the relative abundance of taxa in the core microbiome was significantly correlated to spat age (Figure 3). Similar shifts in microbiome composition with age have been documented in oysters from different life stages (33) and a recent study on the spat microbiome under experimental temperature and pCO2 stress also found a change of the microbiome composition with age (54). A correlation between the microbiome development and host age has also been documented in corals, insects and fish (41, 43, 55, 56).…”
Section: Discussionsupporting
confidence: 77%
“…In the present study the relative abundance of taxa in the core microbiome was significantly correlated to spat age (Figure 3). Similar shifts in microbiome composition with age have been documented in oysters from different life stages (33) and a recent study on the spat microbiome under experimental temperature and pCO2 stress also found a change of the microbiome composition with age (54). A correlation between the microbiome development and host age has also been documented in corals, insects and fish (41, 43, 55, 56).…”
Section: Discussionsupporting
confidence: 77%